Characterization of natural wax esters by MALDI-TOF mass spectrometry - Vrkoslav, Vladimír; Míková, Radka; Cvacka, Josef (Journal of mass spectrometry, 2009)
The applicability of matrix-assisted laser desorption/ionization time of flight mass spectrometry (MALDI-TOF MS) to the analysis of wax esters (WEs) was investigated. A series of metal salts of 2,5-dihydroxybenzoic acid (DHB) was synthesized and tested as possible matrices. Alkali metal (Li, Na, K, Rb, Cs) and transition metal (Cu, Ag) salts were studied. The matrix properties were evaluated, including solubility in organic solvents, threshold laser power that should be applied for successful desorption/ionization of WEs, the nature of the matrix ions and the mass range occupied by them, and the complexity of the isotope clusters for individual metals. Lithium salt of dihydroxybenzoic acid (LiDHB) performed the best and matrices with purified lithium isotopes ((6)LiDHB or (7)LiDHB) were recommended for WEs. Three sample preparation procedures were compared: (1) mixing the sample and matrix in a glass vial and deposition of the mixture on a MALDI plate (Mix), (2) deposition of sample followed by deposition of matrix (Sa/Ma), and (3) deposition of matrix followed by deposition of sample (Ma/Sa). Morphology of the samples was studied by scanning electron microscopy. The best sample preparation technique was Ma/Sa with the optimum sample to matrix molar ratio 1 : 100. Detection limit was in the low picomolar range. The relative response of WEs decreased with their molecular weight, and minor differences between signals of saturated and monounsaturated WEs were observed. MALDI spectra of WEs showed molecular adducts with lithium [M + Li](+). Fragments observed in postsource decay (PSD) spectra were related to the acidic part of WEs [RCOOH + Li](+) and they were used for structure assignment. MALDI with LiDHB was used for several samples of natural origin, including insect and plant WEs. A good agreement with GC/MS data was achieved. Moreover, MALDI allowed higher WEs to be analyzed, up to 64 carbon atoms in Ginkgo biloba leaves extract.
Keywords: vosky; Plant Leaves; Salts; Sensitivity and Specificity; senzitivita a specificita; Lithium; lithium; soli; Wings, Animal; Copper; molekulová hmotnost; Metals, Alkali; gentisáty; Molecular Weight; Solvents; Waxes; zvířata; Silver; listy rostlin; rozpouštědla; měď; Gentisates; Esters; spektrometrie hmotnostní - ionizace laserem za účasti matrice; alkalické kovy; Diptera; stříbro; křídla zvířecí; Ginkgo biloba; Animals; Spectrometry, Mass, Matrix-Assisted Laser Desorption-Ionization; estery